Crustal Structure of the Nankai Subduction Zone Revealed by Two Decades of Onshore‐Offshore and Ocean‐Bottom Seismic Data: Implications for the Dimensions and Slip Behavior of the Seismogenic Zone. Issue 10 (17th October 2022) - Bassett, Dan; Arnulf, Adrien; Kodaira, Shuichi; Nakanishi, Ayako; Harding, Alistair; Moore, Gregory
Abstract: Two‐decades of onshore‐offshore, ocean‐bottom seismometer, and passive‐source data are integrated to obtain high‐resolution 3‐D constraints on the architecture of the Nankai subduction zone. Our model reveals large along‐strike variability in the width of the outer‐forearc, with the crustal backstop ( V P ≥ 5 km/s) extending within 50 km of Nankai Trough offshore Tokai and Kii Peninsula, but is a factor of 2 further landward (90–115 km) offshore Cape Muroto and Kyushu. The crustal backstop broadly coincides with the down‐dip extent of shallow slow‐earthquakes and the up‐dip extent of co‐seismic slip and geodetic locking, suggesting a link with the shallow frictional transition. In the inner‐forearc, high seismic‐velocities ( V P  > 6.6 km/s) in Kii Peninsula reflect Miocene plutons, impacting the nucleation and segmentation of large megathrust earthquakes. The complex geometry of the subducting slab drives spatial variability in the location of the down‐dip frictional transition. Variability in the width of the outer‐forearc, the dip of the subducting slab, and the depth distribution of deep slow‐slip events combine to produce large changes in the width of the seismogenic zone. This is most pronounced across Bungo channel, where the seismogenic zone narrows from 90 to 120 km in Shikoku to <60 km offshore Kyushu. Pinching of the seismogenic zone may explain the smaller area, and thus magnitude, of earthquakes offshore Kyushu and the reduction in slip‐deficit rate. Our results suggest crustal‐scale architecture is a key driver of profound along‐strike transitions in the location of frictional transition zones, and the width and slip behavior of the intervening seismogenic zone at Nankai Trough. Plain Language Summary: Some subduction zones produce the largest earthquakes and tsunami on Earth, while others slip aseismically. To understand what factors impact subduction zone slip behavior, we have integrated dense geophysical datasets that have accumulated over >20 years in SW Japan to construct the first high‐resolution, 3‐D image of an entire subduction zone. This image reveals large variability in the offshore extent of dense, rigid crustal rocks and suggests the position of this crustal backstop may influence the shallow transition from aseismic to seismic slip along the Nankai megathrust. The landward extent of seismic slip is also spatially variable and appears to be predominantly controlled by the geometry of the subducting plate. Collectively, along trench variability in the position of the crustal backstop (up‐dip transition) and the geometry of the subducting slab (down‐dip transition) combine to produce large variability in the width of the seismogenic zone. Earthquake magnitude is proportional to rupture area and pinching of the seismogenic due to the convergence of shallow and deep frictional transitions may explain the smaller magnitude of earthquakes offshore Kyushu. Our results reinforce the importance of crustal scale architecture in modulating earthquake and tsunami hazard at subduction zones. Key Points: Two‐decades of geophysical data suggest the crustal backstop coincides with the up‐dip transition from slow to seismic slip at Nankai Trough Spatial variability in backstop position and subducting slab geometry produce large changes in width of the seismogenic zone along‐strike Pinching of the seismogenic zone between Shikoku and Kyushu may explain reductions in earthquake magnitude and slip‐rate deficit